2018
DOI: 10.4142/jvs.2018.19.6.735
|View full text |Cite
|
Sign up to set email alerts
|

TGF-β1 upregulates the expression of hyaluronan synthase 2 and hyaluronan synthesis in culture models of equine articular chondrocytes

Abstract: We investigated the effect of transforming growth factor beta 1 (TGF-β1) on equine hyaluronan synthase 2 (HAS2) gene expression and hyaluronan (HA) synthesis in culture models of articular chondrocytes. Equine chondrocytes were treated with TGF-β1 at different concentrations and times in monolayer cultures. In three-dimensional cultures, chondrocyte-seeded gelatin scaffolds were cultured in chondrogenic media containing 10 ng/mL of TGF-β1. The amounts of HA in conditioned media and in scaffolds were determined… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 37 publications
2
10
0
Order By: Relevance
“…The production of HA is regulated by growth factors, hormones, inflammatory cytokines and mechanical load. Previous study showed that TGF‐β1 can upregulate HAS2 expression and HA synthesis in culture models of equine articular chondrocytes 17 . A study suggested that IL‐1β is a crucial factor in the fragmentation of HA in inflammatory joints.…”
Section: Discussionmentioning
confidence: 99%
“…The production of HA is regulated by growth factors, hormones, inflammatory cytokines and mechanical load. Previous study showed that TGF‐β1 can upregulate HAS2 expression and HA synthesis in culture models of equine articular chondrocytes 17 . A study suggested that IL‐1β is a crucial factor in the fragmentation of HA in inflammatory joints.…”
Section: Discussionmentioning
confidence: 99%
“…TGF-β1 is an important growth factor involved in the development, growth and maintenance of articular cartilage, although its role in osteoarthritis has not been completely elucidated ( 22 ). Several studies have shown that TGF-β1 supports chondrogenic differentiation of stem cells ( 23 , 24 ) and upregulates hyaluronan synthesis in cultured equine chondrocytes ( 25 ). However, TGF-β1 has also been implicated in osteophyte formation and synovial fibrosis, mainly in murine studies ( 26 , 27 ).…”
Section: Discussionmentioning
confidence: 99%
“…From the circRNA-miRNA-mRNA network, we found that TGF-β1 was a potential downstream target of hsa-miR-29b-3p ( Figure 6). TGF-β1 has been reported to be closely related to HA metabolism and OA pathogenesis (20). Furthermore, a previous study has described the interaction between hsa-miR-29b-3p and TGF-β1 (21).…”
Section: Circhybid Upregulates the Expression Of The Hsa-mir-29b-3p Tmentioning
confidence: 98%